IMPROVING STUDENTS™ ACHIEVEMENT IN WRITING NARRATIVE TEXT THROUGH PROBLEM BASED LEARNING - Siregar, Nurhanna Sari (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
ABSTRACT This study attempted to improve students™ achievement in writing narrative text by applying Problem Based Learning technique. This study was conducted by using clasroom action research. The subject of this research was the students of  VIII science SMP I BARUMUN TENGAH PADANG LAWAS with the total 40 students. The esearches conducted in two cycles consisted of six meetings. The instruments for collecting the date were tests, diary notes, observation sheets, and interview. Based on the date analysis, the mean of the students™ score for the orientation test was 51. 52 for test I (cycle 1) was 39. 61 and for test II (cycle 2) was 58. 76. The conclution is Problem Based Learning technique can improve the students™ achievement in writing narrative text. Keywords: Problem Based Learning, Writing, Narrative Text